The Effect of Work Environment and Work Discipline on The Effect of Work Environment, Work Discipline on Employee Performance with Communication as an Intermediate Variable - Wirawan, Maryani; Putri, Christin (Journal of Social Science and Business Studies, 2023)
This study aims to examine the influence of the work environment and work discipline on employee performance through communication. The population in this study is all employees. The sample in this study consisted of 129 employees. This study uses a census sampling technique. Data collection techniques obtained using interviews and questionnaires. Based on the results of the analysis of hypothesis testing, it can be found that the accepted hypothesis (influence) is that the work environment has an influence on communication, work discipline has an influence on communication, the work environment has an influence on performance, work discipline has an influence on performance, and the work environment and work discipline have an influence on performance through communication as an intervening variable. The hypothesis that is neither rejected nor accepted is that the work environment has an influence on communication